Zakarpattia committee of the CPU in a national-religious revival of the late 1980s. ХХ century - Vasyl Chura (Cхід)
One of the key consequences of the introduction of political reforms in the USSR within the framework of perebudovnih innovations, was the revival of Ukrainian national consciousness, which weakened the political principles of the ruling CPSU-CPU and caused his active opposition to attempts to restore the state independence of Ukraine. The most poignant of these processes have been deployed in Western Ukraine, where ethnic consciousness was dominant. Therefore, scientific exploration sets causes and traces the dynamic deployment of national-religious revival among patriotic minded public of zakarpatska oblast of Ukrainian SSR against the background of its perception by the communist leadership in the region in the late 1980-ies.